2019
DOI: 10.17794/rgn.2019.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Stream Sediments Pollution by Potentially Toxic Elements in the Active Mining Area of Okpella, Edo State, Nigeria

Abstract: An active gold mining area in Okpella, Edo State, Nigeria was studied to assess the contribution of gold mining to the concentrations of potentially toxic elements (PTEs) in stream sediments. Standard geochemical sampling and sample method. The concentrations of arsenic (As), cobalt (Co), chromium (Cr), copper (Cu), mercury (Hg), nickel (Ni), lead I geo) were calculated-ate enrichment of Cu, minor enrichment of As and Pb, and no enrichment of Co, Cr, Ni and Zn in the sediments. The I geo also showed that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Collected samples were analyzed by the ICP-OES method [36][37][38][39]. Studies and results of stream sediment samples identified some points with a higher grade than the cut-off limit [40]. The specimens identified as anomalies of copper, silver, manganese, lead, and zinc are shown in Figure 6.…”
Section: Geochemistrymentioning
confidence: 99%
“…Collected samples were analyzed by the ICP-OES method [36][37][38][39]. Studies and results of stream sediment samples identified some points with a higher grade than the cut-off limit [40]. The specimens identified as anomalies of copper, silver, manganese, lead, and zinc are shown in Figure 6.…”
Section: Geochemistrymentioning
confidence: 99%
“…Because metals are irreversible and have harmful impacts on living creatures, determining the heavy metal concentration of soils around cement plants should be part of the environmental monitoring and evaluation process. Despite the fact that Obaje et al (2019) investigated the degree of heavy metal pollution in stream sediments in Okpella's active mining region, the results indicated that stream sediments in this location are heavily polluted by potentially harmful metals (PTM). However, no research had been done to identify the number of heavy metals in the area's soils.…”
Section: Introductionmentioning
confidence: 97%
“…Although the human contribution of Hg to the environment is mainly caused by the use of Hg in gold extraction and the burning of fossil fuels, contamination of the hydrographic basin can also result from atmospheric deposition, inadequate waste disposal, as well as leaching of agricultural soil [10][11][12][13]. Thus, although studies are generally focused on regions with activities with more significant impacts, it is essential to investigate regions without clear point sources of Hg contamination, looking for areas potentially contaminated by diffuse sources of Hg or with specific characteristics for mobilization and bioaccumulation of this element [14,15].…”
Section: Introductionmentioning
confidence: 99%